Effect of Behavioural Training Programme on Nutritional Factors of Children with Autism Spectrum Disorder: Two Group Pretest Post-test Time Series Design - PC Indu; A Gowrishankar; R Vijayaraghavan; KM Riaz; KS Dinesh; A Shilpapa; KN Vishnupriya; P Thenmozhi (Journal of Clinical and Diagnostic Research)
Introduction: Children with Autism Spectrum Disorder (ASD) are nutritionally vulnerable as they exhibit a selective eating pattern. Evidence shows that 40-85% of children with ASD demonstrate food selectivity, which is attenuated by dietary restrictions such as gluten-free/casein-free diets, imposed as a therapeutic approach to improve their gastrointestinal symptoms. Although inadequate micronutrient and macronutrient intakes are increasingly reported, there are inconsistent results regarding the extent of nutrient deficiencies. Aim: To analyse the effectiveness of a behavioural training programme on the nutritional factors of children with ASD. Materials and Methods: A two-group pretest post-test time series design was adopted for the study. The research was conducted at the Ayurveda and Therapeutic Integration for Developmental Habilitative Intervention (ATIDHI) group in Changaramkulam and the SELF Learning and Counselling Centre in Thrissur, Kerala. The duration of the intervention was six months, with the data collection period occurring between November 2023 and January 2025. A total of 60 parents and their children with ASD were recruited for the study. Parents of children with ASD aged between 3-10 years, who exhibited mealtime behaviours {Brief Autism Mealtime Behaviour Inventory (BAMBI) Score ≥34}, were selected for the study. Demographic parameters of the parents (relation to the child, age, education, occupation and type of family) and demographic data of the children (gender, age, age at diagnosis, gestation, birth weight (kg), birth order and co-morbidities) were collected. A 24-hour dietary recall of the children and their Body Mass Index (BMI) were analysed (O1). The behavioural training programme was administered to the experimental group and post-tests (O2 and O3) were conducted in the 3rd and 6th months. Results: Behavioural training was effective in improving the nutrient adequacy of energy, fibre, retinol, calcium and iron in children with ASD compared to the control group. The behavioural training programme was not effective in improving the BMI of the children (p-value=0.866). There was a significant association between age, sex and BMI with total energy consumption in children with autism. Conclusion: The authors concluded that individualised dietary management based on a behavioural intervention approach is essential to maintain the nutritional status of children with ASD. The aim of the study was to analyse the effectiveness of the behavioural training programme on the nutritional factors of children with ASD.